2019
DOI: 10.1101/650598
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stimulus presentation rates affect performance but not the acquired knowledge – Evidence from procedural learning

Abstract: Presentation rates -the tempo in which we encounter subsequent items -can alter both our behavioral and neural responses in cognitive domains such as learning, memory, decisionmaking, perception and language. However, it is still unclear to what extent presentation rates affect the momentary performance versus the underlying cognitive function or mentalrepresentation. Here we systemically tested the effect of presentation rate on performance versus competence in procedural learning -a fundamental cognitive fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Moreover, the lack of differences persisted even after the normalization of the baseline scores. The fact that the sequence knowledge was comparable to the single-task group in both phases (in the dual-task blocks and in the inserted probe blocks) indicates that the secondary task affected neither the performance nor the competence of the primary task (Kiss, Nemeth, & Janacsek, 2019;Vekony et al, 2019). These results are also in harmony with previous research that found intact implicit sequence knowledge after practicing the primary task in single-task conditions (Frensch et al, 1998;Shanks & Channon, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the lack of differences persisted even after the normalization of the baseline scores. The fact that the sequence knowledge was comparable to the single-task group in both phases (in the dual-task blocks and in the inserted probe blocks) indicates that the secondary task affected neither the performance nor the competence of the primary task (Kiss, Nemeth, & Janacsek, 2019;Vekony et al, 2019). These results are also in harmony with previous research that found intact implicit sequence knowledge after practicing the primary task in single-task conditions (Frensch et al, 1998;Shanks & Channon, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the lack of differences persisted even after controlling for the differences in baseline reaction times. The fact that the probabilistic sequence knowledge of the dual-task group was comparable to that of the single-task group both in the dual-task blocks (performance) and in the intermittent control blocks (competence) indicates that the secondary task did not affect the performance or the competence of the primary task [ 35 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following the standard analysis and interpretation of the task outlined in previous studies 34 , 36 , 61 , incidental use of knowledge (i.e., without intentional access to their knowledge) is sufficient to achieve good performance (that is, producing high-probability triplets above chance level) in the Inclusion condition. In contrast, good performance in the Exclusion condition (that is, producing high-probability triplets at or below chance level) requires intentionally accessible knowledge to exert control over their responses and generate a series of responses that is indeed different from what they practiced (i.e., intentionally exclude the acquired knowledge).…”
Section: Methodsmentioning
confidence: 99%